2012
DOI: 10.1021/cn300105c
|View full text |Cite
|
Sign up to set email alerts
|

Identification in Silico and Experimental Validation of Novel Phosphodiesterase 7 Inhibitors with Efficacy in Experimental Autoimmune Encephalomyelitis Mice

Abstract: A neural network model has been developed to predict the inhibitory capacity of any chemical structure to be a phosphodiesterase 7 (PDE7) inhibitor, a new promising kind of drugs for the treatment of neurological disorders. The numerical definition of the structures was achieved using CODES program. Through the validation of this neural network model, a novel family of 5-imino-1,2,4-thiadiazoles (ITDZs) has been identified as inhibitors of PDE7.Experimental extensive biological studies have demonstrated the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…In the present work, we show that allosteric modulation of both PDE7 and GSK-3, using 5-imino-1,2,4-thiadiazoles: (i) reduces symptoms in the EAE animal model of demyelination (as previously reported36) and, (ii) enhances remyelination in two other demyelinating mouse models where demyelination occurs with minimal adaptive immune system contribution (using lysophosphatidylcholine-LPC- or cuprizone). Our results lead us to propose these dual PDE7-GSK3 inhibitors, especially VP3.15 with its good oral bioavailability and CNS penetration, as potential combined anti-inflammatory and pro-remyelinating therapies for MS.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…In the present work, we show that allosteric modulation of both PDE7 and GSK-3, using 5-imino-1,2,4-thiadiazoles: (i) reduces symptoms in the EAE animal model of demyelination (as previously reported36) and, (ii) enhances remyelination in two other demyelinating mouse models where demyelination occurs with minimal adaptive immune system contribution (using lysophosphatidylcholine-LPC- or cuprizone). Our results lead us to propose these dual PDE7-GSK3 inhibitors, especially VP3.15 with its good oral bioavailability and CNS penetration, as potential combined anti-inflammatory and pro-remyelinating therapies for MS.…”
supporting
confidence: 85%
“…apremilast. The PDE7-GSK3 inhibitors used here (VP3.15 and VP1.15) have previously also shown an immunomodulatory effect in spinal cord injury models (as well as EAE)3436, without emetic side effects3640.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, recent studies showed that PDE7 inhibitors could play an anti‐inflammatory and neuroprotective role in cellular and animal models of Parkinson's disease (Morales‐Garcia et al ., ), spinal cord injury (Paterniti et al ., ), Alzheimer's disease (Perez‐Gonzalez et al ., ) and stroke (Redondo et al ., ). In addition, different chemically diverse PDE7 inhibitors have shown efficacy in the EAE model of MS (Redondo et al ., 2012a,b) without inducing emesis (Garcia et al ., ) pointing to a new era of innovative drugs. In this regard, the therapeutical potential for MS treatment of the thioxoquinazoline derivative TC3.6 synthesized in our laboratory has been recently reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the difficulties to separate beneficial anti‐inflammatory from adverse emetic effects of PDE4 inhibitors, efforts have been focused on finding inhibitors of other PDE that might provide therapeutic alternatives. Special interest has been directed to PDE7 inhibition as an anti‐inflammatory strategy (Smith et al ., ; Giembycz and Smith, ; Castano et al ., ; Jerez et al ., ), and some promising results using PDE7 inhibitors in EAE have been recently reported (Redondo et al ., 2012a; 2012b).…”
Section: Introductionmentioning
confidence: 99%